2022
DOI: 10.1109/tmi.2022.3199483
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Matrix Imaging—Part II: The Distortion Matrix for Aberration Correction Over Multiple Isoplanatic Patches

Abstract: This is the second article in a series of two which report on a matrix approach for ultrasound imaging in heterogeneous media. This article describes the quantification and correction of aberration, i.e. the distortion of an image caused by spatial variations in the medium speed-of-sound. Adaptive focusing can compensate for aberration, but is only effective over a restricted area called the isoplanatic patch. Here, we use an experimentally-recorded matrix of reflected acoustic signals to synthesize a set of v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Here, this property does not hold because the NAFZ subsurface exhibits a continuous but fluctuating reflectivity (see Text S3 in Supporting Information S1). In this scattering regime, local distortion matrices should be considered over restricted areas in which the isoplanatic hypothesis is ideally fulfilled (Lambert, Cobus, et al., 2022; Najar et al., 2023).…”
Section: Matrix Approach For Adaptive Focusing: the Local Distortion ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Here, this property does not hold because the NAFZ subsurface exhibits a continuous but fluctuating reflectivity (see Text S3 in Supporting Information S1). In this scattering regime, local distortion matrices should be considered over restricted areas in which the isoplanatic hypothesis is ideally fulfilled (Lambert, Cobus, et al., 2022; Najar et al., 2023).…”
Section: Matrix Approach For Adaptive Focusing: the Local Distortion ...mentioning
confidence: 99%
“…By removing the geometrical component of the CLASS wave‐field, spatial correlations are highlighted between distorted wave‐fields induced by neighbor virtual sources rin ${\mathbf{r}}_{\text{in}}$ (Badon et al., 2020). Such correlations are a manifestation of a spatial invariance of residual aberrations over areas generally referred to as isoplanatic patches (Lambert, Cobus, et al., 2022).…”
Section: Matrix Approach For Adaptive Focusing: the Local Distortion ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As opposed to methods that model the phase aberration effect by a fixed near-field phase screen in front of the transducer, the locally adaptive phase aberration correction technique [14] assumed a spatially varying near-field phase screen and employed multistatic synthetic aperture data to perform the correction at each point adaptively. Lambert et al suggested compensating for the spatially-distributed aberrations by decoupling aberrations undergone by the outgoing and incoming waves utilizing the distortion matrix built from the focused reflection matrix, which contains the responses between virtual transducers synthesized from the transmitted and received focal spots [15], [16], [17].…”
Section: A Related Workmentioning
confidence: 99%
“…To do so, we rely on the concept of change of basis from the canonical sensor basis to a Rx plane waves (PWs) basissometimes denoted as Radon domain-proposed recently [25], [26]. Following [20], [24], the main rationale behind the proposed method is to express the data into a local Rx PW basis to account for the locality of the phase aberrations induced by SoS variations.…”
Section: Introductionmentioning
confidence: 99%